Assessment of Daphnia magna as a toxicity bioindicator for wastewaters - Serra, Adriana Magalhães de Castro (2019)
Toxicity tests on complex wastewater effluents have been considered as an important complement to emission limit values (ELV) based on physico-chemical and microbiological parameters in recent years. However, relatively few studies have been conducted so far evaluating the toxicity of effluents with aquatic organisms, and it remains unclear which test species should be used in such evaluations. The first aim of this dissertation was therefore to assess the potential of the crustacean Daphnia magna as a bioindicator for the toxicity of a domestic effluent disinfected with peracetic acid (PAA), a disinfect that has received increasing attention in recent years as an alternative disinfectant for chloride. To this end, bioassays were performed with D. magna on the secondary effluent from the WWTP of Beirolas, with and without disinfection by 5 mg.L-1, 10 mg.L-1 and 15 mg.L-1 PAA. These PAA concentrations were selected since they were shown in a parallel MSc study to have high removal efficacy of coliform and faecal bacteria. Exposure to the secondary effluent without disinfection caused no mortality or immobility on the organisms. Although the disinfected effluent adhered to all the standards set in current Legislation, even the lowest PAA concentration resulted in 100% daphnid mortality within 48h. Subsequently, efforts should be made to evaluate whether lower PAA concentrations or a longer residual time after PAA treatment may ensure disinfection efficacy without exerting toxicity to aquatic organisms like D. magna. The second aim of this dissertation was to compare the sensitivity of D. magna to wastewater with that of other species commonly used in bioassays. This was done to evaluate which test species are the most appropriate for use in wastewater toxicity testing. To this end, a literature search was conducted by collecting data from papers where the toxicity of effluents was tested to D. magna and at least one other species. This thus allowed to evaluate the relative tolerance (Trel) of these species as compared to D. magna. The taxonomic groups that appeared to be more sensitive to effluents than D. magna were bacteria and rotifers. On the other hand, macrophytes, insects and fish were found to be generally less sensitive than D. magna. Since no single species was aways the most sensitive species to the wide range of effluents (e.g. different sources, compositions and sampling periods) included in the dataset, a test battery including species from different taxonomic groups is recommended for effluent testing.